The use of option-implied volatility in forecasting future volatility and returns - Hänninen, Anton (My University, 2025)
The purpose of this thesis is to examine the forecasting capabilities of option-implied metrics in forecasting future volatility and asset returns. Implied volatility is compared with ex-post forecasting methods such as GARCH models to determine whether a single approach can be considered the most effective for volatility forecasting, particularly within equity markets. While U.S. equity markets serve as the main focus, other asset classes and geographical markets are also reviewed. Additionally, the effects of market conditions and investor sentiment on volatility forecasting are explored. The findings indicate that although implied volatility is generally regarded as a reliable method for volatility forecasting, no single approach can be determined to be universally superior. Combinations of different methods often yield the highest forecasting accuracy. In addition, the study finds that implied volatility contains valuable information that can be utilized in forecasting future returns.

Tämän opinnäytetyön tarkoituksena on tutkia optioista johdetun tiedon käyttöä tulevan volatiliteetin ja tuottojen ennustamisessa. Implisiittistä volatiliteettia verrataan ennustemenetelmiin, jotka hyodyntävät toteutunutta volatiliteettiä, tarkoituksena selvittää, voidaanko yhtä lähestymistapaa pitää kaikkein tehokkaimpana volatiliteetin ennustamisessa erityisesti osakemarkkinoilla. Vaikka Yhdysvaltain osakemarkkinat ovat pääasiallisena tarkastelun kohteena, myös muita omaisuusluokkia ja markkinoita otetaan huomioon. Lisäksi työssä tutkitaan markkinaolosuhteiden vaikutuksia volatiliteetin ennustamiseen. Tulokset osoittavat, että vaikka implisiittistä volatiliteettia pidetään yleisesti luotettavana menetelmänä volatiliteetin ennustamiseen, mitään yksittäistä lähestymistapaa ei voida pitää ylivoimaisena. Eri menetelmien yhdistelmät tuottavat usein tarkimmat ennusteet. Lisäksi tutkimus osoittaa, että implisiittinen volatiliteetti sisältää arvokasta informaatiota, jota voidaan hyödyntää tulevien tuottojen ennustamisessa.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|